Comparative Design of Structures Concepts and Methodologies - Lin, Shaopei; Huang, Zhen.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book presents comparative design as an approach to the conceptual design of structures. Primarily focusing on reasonable structural performance, sustainable development and architectural aesthetics, it features detailed studies of structural performance through the composition and de-composition of these elements for a variety of structures, such as high-rise buildings, long-span crossings and spatial structures. The latter part of the book addresses the theoretical basis and practical implementation of knowledge engineering in structural design, and a case-based fuzzy reasoning method is introduced to illustrate the concept and method of intelligent design. The book is intended for civil engineers, structural designers and architects, as well as senior undergraduate and graduate students in civil engineering and architecture. Shaopei Lin and Zhen Huang are both Professors at the Department of Civil Engineering, Shanghai Jiao Tong University, China.
Introduction of Design Philosophy -- Introduction to Structural Design -- Global Design of Structures -- Systematic Analyses of Sub-structures -- Comparative Design and Analyses of High-rise Buildings -- Comparative Design and Analyses of Long-span Crossings Structures -- Comparative Design and Analyses of Spatial Structures -- Intelligent Design Based on Knowledge Engineering.
Keywords: Buildings -- Design and construction; Architecture; Buildings; Engineering design; Computational intelligence; Building Construction and Design; Building Types and Functions; Engineering Design; Computational Intelligence